The Story Of Prophet Salih - "Khan, Saniyasnain" (China: goodwordbooks, 2024)
The Story of Prophet Salih (AS) is a delightful board book that makes a perfect gift for little children. This book introduces young readers to the inspiring Quranic story of Prophet Salih, who was sent to guide his people with wisdom and patience. Told in simple and engaging language, the story highlights the miracles and lessons from his life, helping children understand the importance of faith, obedience, and listening to good advice. The vibrant illustrations bring the story to life, capturing the imagination of little ones as they journey through this timeless tale. At the end of the book, a meaningful moral encourages children to reflect on the values taught by Prophet Salih. With its durable board book format, it$1 (Bs designed for little hands and repeated reading, making it a cherished addition to any child$1 (Bs Islamic library.s